ScudADL: An architecture description language for adaptive middleware in ubiquitous computing environments - Qing Wu; Ying Li (2009 ISECS International Colloquium on Computing, Communication, Control, and Management, 2009)
With the increasing demands for adaptive middleware of dynamic systems in ubiquitous computing environments, the need for dynamic software architecture and programming infrastructure to achieve dynamic adaptation is widely recognized. The paper firstly presents a semantic and adaptive middleware architecture called ScudWare that supports for ubiquitous computing environments. Specially, a Scud-ADL framework and the specification semantics, based on higher-order typed pi calculus theory, are proposed, which describes ScudWare component structure characters, and dynamic behavior adaptation. In the ScudADL, the computing resources consumption is concerned. And the component inner and outer adaptive behaviors are separated from component functional behaviors in an explicit way. Finally, we give a case study to show its adaptation.